Distribuição das tensões em overdentures mandibulares em função do número de implantes e tipo de conexão quando submetidos a carregamento oclusal: análise fotoelástica e extensométrica - Borges, Anna Clara Mendes [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The consensus statement recommends at least two implants to support a mandibular overdenture for edentulous patients. However, to reduce cost and time of treatment, the concept of single implant-retained overdentures provides another option. Nonetheless, the optimal number of implants required to retain a mandibular overdenture is still under evaluation. The objective of this study was to evaluate the biomechanical behavior of overdentures supported by 1 or 2 implants with different types of connections and submitted to compression, by photoelastic analysis (PA) and strain gauge analysis (SGA). Based on a cast of an edentulous mandible, the specimens were divided in 4 groups of 1 specimen each for the PA and 4 groups of 5 specimens each for the SGA, divided by the type of connection (Morse taper and external hexagon) and the number of implants (1 or 2). For PA, the photoelastic implant/prosthesis cast assembly was positioned in a circular polariscope associated with a universal testing machine (EMIC) and applying compression. The tension generated was photographed and analyzed qualitatively. For SGA, 2 strain gauges were positioned on the mesial and distal of each implant and the electrical signals were captured by a data acquisition device (ASD2001). The data were submitted to ANOVA and the Bonferroni test (P<0.0001) Through PA, the greatest number of tension fringes in both connection types was presented by the two- implant supported overdentures when compared with the single-implant supported overdentures. Through SGA, a statistical difference was verified between the connections in groups with 1 implant (P<0.0001), with the Morse taper having the lowest microstrain values. The lowest tension values in both types of connections were presented by the overdentures with 1 implant (P<0.0001). It was concluded that the number of implants directly influenced the distribution of tension in both forms...

A literatura recomenda o uso de ao menos dois implantes para suportar uma overdenture mandibular em pacientes completamente edêntulos. No entanto, para reduzir o custo e tempo de tratamento, o conceito de overdenture sob um único implante surge como uma ótima opção. No entanto, ainda há divergências de opiniões quanto à quantidade ideal de implantes necessários para reter uma overdenture mandibular. O objetivo deste estudo foi avaliar por meio de análise fotoelástica (AF) e extensométrica (AE), o comportamento biomecânico de overdentures retidas por 01 ou 02 implantes com diferentes tipos de conexões, submetidas à compressão. A partir de um modelo de uma mandíbula edêntula, os espécimes foram divididos em 04 grupos de 01 espécime cada para AF e 04 grupos de 05 espécimes cada para AE, divididos pelo tipo de conexão (cone morse e hexágono externo) e número de implantes (01 ou 02). Para AF, o conjunto modelo fotoelástico/implante/prótese foi posicionado em um polariscópio circular associado a uma máquina de ensaio universal (EMIC), sendo aplicada força de compressão de 100N. As tensões geradas foram registradas fotograficamente e analisadas qualitativamente. Para AE, 2 extensômetros foram posicionados (mesial e distal de cada implante) e os sinais elétricos captados por um aparelho de aquisição de dados (ASD2001). Os dados foram submetidos a ANOVA e ao teste Bonferroni (P<0.0001). Pela AF, as overdentures retidas por 02 implantes apresentaram maior número de franjas de tensão em comparação com as retidas por 01 implante, em ambas conexões. Pela AE, houve diferença estatística entre as conexões nos grupos com 01 implante (P<0.0001), sendo o cone morse com menores valores de microstrain. As overdentures com 01 implante apresentaram menores valores de tensão do que as com 02 implantes, em ambas as conexões (P<0.0001). Conclui-se que o número de implantes...
Keywords: Implantes dentários; Biomecânica; Prótese dentária fixada por implante; Dental implants